Exploring waste utilization potential: nutritional, functional and medicinal properties of oilseed cakes - Vichare, Sharvary Arun; Morya, Sonia (Frontiers in Food Science and Technology, 2024)
Nowadays, oilseed cakes are the by-products of oil extraction, have gained significant interest due to their wide range of nutritional, functional, and medicinal properties. The review paper is an overview of the applications of oilseed cakes across due to their nutritional and economic potential. Oilseed cakes present a valuable resource due to rich nutritional profile and potential health advantages. These by-products of oil extraction are not only abundant in proteins, fibres, and essential micronutrients but also possess functional and medicinal properties that can enhance food security and promote overall health. Their utilization in food systems support sustainable agricultural practices, waste reduction, and the development of functional foods, thereby contributing to better health outcomes and a holistic approach to wellbeing aligning with broader sustainable development goals. Overall, this paper underscores the importance of diligent exploration into the multifaceted properties of oilseed cakes, offering valuable insights into their potential applications and avenues for further research and development.